INVESTIGATING ENGLISH DEPARTMENT STUDENTSâ PERCEPTIONS ABOUT A GOOD ENGLISH LANGUAGE TEACHER - Febriyanti, Emma Rosana (Universitas Negeri Makassar, 2018)
Teaching is a lifelong learning process and even if a teacher may have years of experience in teaching English as a foreign language, one might not know whether he/she has become a good teacher or not. The perceptions about a âgoodâ English language teacher have been varied among the language learners and the teachers themselves. However, it is important to find out what kind of a âgoodâ English language teacher based on learnersâ perceptions in order to discover what they believe and what they expect from their English teachers when they are learning the language. This present study aims at investigating and describing the qualities or the characteristics of a good English teacher based on the learners perceptions. The population for this study are the students of English Department of FKIP Lambung Mangkurat University Banjarmasin in three batches (batch 2015, 2016, and 2017), and when the time data collected they were at the sixth, the fourth and the second semester. The questionnaire given is in the form of close-ended questions and analysed quantitatively. The findings of this study are expected to help teachers to reflect or evaluate themselves and refresh their teaching practice when necessary, as well as for their own improvement and further professional development.